Effect of Fish Proteins, Salt, Sugar and Monosodium Glutamate on the Microstructural, Rheological and Physico-Chemical Properties of Fish Cracker ('Keropok') - Cheow, Chong Seng (1998)
Fish cracker or more commonly known as 'keropok' in Malaysia is a popular snack food among countries in the ASEAN region. This work examines factors affecting 'keropok' quality such as the effect of fish proteins, salt. sugar, monosodium glutamate (MSG) on the gelatinisation of tapioca and sago st arches. Microstructural studies of 'keropok' during different stages of processing were al so observed and correlated to rheological behaviour. Results from differential scanning calorimetry (DSC) showed that with increasing fish content the conclusion gelatinisation temperature (Tc) of the mixture remained relatively constant while the range of gelatinisation temperature decreased. There were hardly any effect due to the addition of 1% sugar and 0.4% MSG. on the onset (To) and peak(Tp) gelatinisation temperatures of sago and tapioca starches. The addition of 2% salt had the greatest effect on gelatinisation temperature of 'keropok' mixture, linear expansion of fried'keropok',and small and large deformations of 'keropok' gel. The technology of producing a good expanded 'k that fresh fish, sufficient amount of salt (2% of the total weight of wet fish and starch), proper sequence of mixing of the 'keropok' mixture to form evenly distributed fiexpansion, full gelatinisation of fish-starch gel, and elastic fish-starch gel formation. At high fish contents (60-70%) the formation of fish protein network in the matrix caused a drop in expansion. There was, however, a sharp increase in the compressive strength of the 'keropok' gel. This result is complemented by the higher storage modulus (G') and lower loss tangent (tan ᵟ) values obtained, indicative of the existence of a strong elastic network. Such conditions were observed when the microstructure of the fish muscle fibres appeared to be well crosslinked. The findings in this study revealed that in order to produce better expanded 'keropok' and a more elastic and fully gelatinised 'keropok' gel, superior interms of appearance, shape and linear expansion, several important factors that ensure even distribution of fish proteins in the fish-starch gel must be taken into account. In conclusion, fresh fish, sufficient amount of salt (2% of the weight of wet fish and starch) and the proper sequence of adding ingredients in mixing are recommended to produce high quality ' keropok'.